Influence of Intellectual Capital on Financial Distress in Retail Sub-Sector Companies on Indonesia Stock Exchange - Sisca; Putri, Debi Eka; Putra, Hendrick Sasimtan; Siregar, Liper; Aswatama, Gian (EAJ (Economic and Accounting Journal), 2024)
The purpose of this study is to examine: 1. The overview of intellectual capital and financial distress in retail sub-sector companies listed on the Indonesia Stock Exchange. 2. The influence of intellectual capital on financial distress in retail sub-sector companies listed on the Indonesia Stock Exchange. This study employs a library research design and uses data from all retail sub-sector companies on the Indonesia Stock Exchange on December 31, 2022. The study applies qualitative and quantitative descriptive analysis with purposive sampling techniques. Methods used for data analysis and testing include hypothesis testing, correlation and determination coefficients, simple linear regression analysis, and classical assumption tests. The study draws two main conclusions: 1. Intellectual capital and financial distress fluctuate and tend to decline over time. 2. According to the simple linear regression analysis, intellectual capital has a positive but insignificant effect on financial distress. The coefficient of determination test results indicate that intellectual capital contributes only a small portion to financial distress. The correlation coefficient test results show a very weak relationship between intellectual capital and financial distress.